2014
DOI: 10.1111/dom.12282
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for severe hypoglycaemia in treated type 2 diabetes mellitus patients in the UK – a nested case–control analysis

Abstract: Severe hypoglycaemia was recorded in 12 cases per 10,000 PYs. Risk factors for severe hypoglycaemia included increasing age, renal failure, cognitive impairment/dementia, and current use of insulin or sulphonylureas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…In contrast, the independent determinants of severe hypoglycemia were older age, limited education, hypertension, renal insufficiency, and mild cognitive impairment. These observations are also consistent with those of other reports (5,(13)(14)(15)(16)(17). Stated in clinically relevant terms, these analyses suggest that an individual with a BMI of 25 kg/m 2 would be ;30% more likely to have nonsevere hypoglycemia than one with a BMI of 35 kg/m 2 , but with no difference in the risk of severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the independent determinants of severe hypoglycemia were older age, limited education, hypertension, renal insufficiency, and mild cognitive impairment. These observations are also consistent with those of other reports (5,(13)(14)(15)(16)(17). Stated in clinically relevant terms, these analyses suggest that an individual with a BMI of 25 kg/m 2 would be ;30% more likely to have nonsevere hypoglycemia than one with a BMI of 35 kg/m 2 , but with no difference in the risk of severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, reasons and clinical circumstances for SH may be multifactorial and complex. Apart from the established individual risk factors such as age, diabetes duration, mode of therapy, comorbidity, comedication, impaired awareness of hypoglycemia, physical activity or alcohol consumption (Bruderer et al, 2014;Holstein et al, 2012;Pedersen-Bjergaard et al, 2004), further predisposing conditions could be of clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Severe hypoglycaemia was found to be prevalent in almost half of people with long-duration type 1 diabetes. 32 A retrospective cohort study by Bruderer et al 33 found severe hypoglycaemia was recorded in 12 cases per 10 000 person-years in patients with type 2 diabetes in the United Kingdom who were newly treated with anti-diabetic drugs.…”
Section: Introductionmentioning
confidence: 99%